Meet the Expert : Neal Ford on Invalidating Axioms in Software Architecture - Ford, Neal (O'Reilly Media, Inc., 2020)
The software ecosystem changes chaotically: one small change causes another; when repeated hundreds of times, it generates a new ecosystem. In fact we must question fundamental axioms on a regular basis, in light of improved engineering practices, operational ecosystems, software development processes-everything that makes up the messy, dynamic equilibrium where architects and developers work each day. Careful observers of software architecture over time have witnessed a slow evolution of capabilities. From the engineer practices of extreme programming to continuous delivery, the DevOps revolution, microservices, containerization, and now cloud-based resources, all of these innovations have led to new capabilities and trade-offs. Expert Neal Ford looks at software architecture in a modern light, taking into account all the innovations from the last decade, along with some new metrics and measures suited to the new structures and perspectives now available. Recorded on February 19, 2020. See the original event page for resources for further learning or watch recordings of other past events . O'Reilly Meet the Expert explores emerging business and technology topics and ideas through a series of one-hour interactive events. You'll engage in a live conversation with experts, sharing your questions and ideas while hearing their unique perspectives, insights, fears, and predictions.